2001
DOI: 10.1073/pnas.191199198
|View full text |Cite
|
Sign up to set email alerts
|

Furin inhibition results in absent or decreased invasiveness and tumorigenicity of human cancer cells

Abstract: Pro-protein convertases such as furin are expressed in many human tumor lines and primary tumors. Furin processes stromelysin-3, membrane type 1 matrix metalloproteinase (MMPs) involved in tumor cell invasiveness, as well as growth factors such as transforming growth factor ␤1. Evaluation of furin expression in head and neck squamous cell carcinoma (HNSCC) cells exhibiting different invasive ability showed that furin overexpression correlated with their respective invasiveness. The use of a selective furin inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 33 publications
2
130
0
3
Order By: Relevance
“…We, and others, previously observed that PCs inhibition leads to delayed tumor development and reduced tumor volume in nude or immunodeficient mice. [22][23][24][25] However, herein we used immunosuppressed newborn rats to test the metastatic dissemination. Results obtained with this animal model show that the role of PCs in tumor development and progression is far from being as simple as suggested by previous observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We, and others, previously observed that PCs inhibition leads to delayed tumor development and reduced tumor volume in nude or immunodeficient mice. [22][23][24][25] However, herein we used immunosuppressed newborn rats to test the metastatic dissemination. Results obtained with this animal model show that the role of PCs in tumor development and progression is far from being as simple as suggested by previous observations.…”
Section: Discussionmentioning
confidence: 99%
“…49 Differences in stromal microenvironment might thus explain the discrepancies between the present in vivo results and invasion assays using tracheal xenotransplants. 22,25 Given the role of PCs in biological activation of inactive precursors, their inhibition could be an interesting clinical strategy against cancers by simultaneously disrupting the function of numerous proteins involved in tumor cell invasion and tumor progression. 15,20 However, the effect of ␣1-PDX on certain convertase substrates, like adhesion molecules, MMPs or other proteases, that could potentially contribute to tumorigenesis should be taken into account when considering PC inhibitors as therapeutic tools for a variety of diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that a portion of the cellular MT1-MMP pool is processed by additional PCs and also by autocatalysis directly at the cell surface (Sato et al, 1999;Yana and Weiss, 2000;Rozanov and Strongin, 2003;Deryugina et al, 2004). Inhibition of MT1-MMP activation by furin inhibitors, including a nanomolar range a1-anti-trypsin variant Portland (PDX) inhibitor repressed motility and tumorigenicity of cancer cells (Bassi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…11 Furin inhibition with ␣-1 PDX, a specific inhibitor of this PC, 12 demonstrated that the levels of processed MT1-MMP as well as the invasion ability of cells was greatly diminished in head and neck squamous cell carcinoma (HNSCC) cell lines. 13 On the other hand, some reports argue that MT1-MMP can be activated in a furin-independent manner suggesting that, at least in some systems, furin may not be crucial to tumor progression. 14 Furin can process another metalloproteinase, stromelysin-3, 15 which is able to degrade ␣-1 proteinase inhibitor, a serin protease inhibitor, 16 contributing to enhance extracellular matrix turnover.…”
mentioning
confidence: 99%